Annual report readability and stock return synchronicity: Evidence from India - Vismaya Gangadharan; Lakshmi Padmakumari (Cogent Economics & Finance, 2023)
This study investigates the relationship between the comprehensibility of a firm's annual report and its stock return synchronicity in the Indian market. The study employs the readability of annual reports as a measure for the cost of information processing. The findings suggest that firms with more readable annual reports tend to display higher stock return synchronicity. This relationship implies that more legible financial disclosures are associated with more efficient and transparent capital markets. Additionally, the research discovered that the relationship between readability and stock return synchronicity is particularly pronounced for companies with high institutional investment, high analyst coverage, and lower information asymmetry. The sample size of the study encompasses NSE 500 companies for the period 2015-2016 to 2019-2020.
Keywords: G10; G14; 330; Analyst following; Annual report readability; Information asymmetry; Institutional investors; Synchronicity